The Management of Work Risk for a Plate Rolling Mill Machine - Marian BORDEI; Stefan DRAGOMIR; Viorel DRAGAN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2013)
Arcelor Mittal is the leader on important iron and steel global markets. This company has a performant system for research, for iron and steel plate production and has a top network for distribution, too. The company has production units in 20 countries on 4 continents, in all key markets of iron and steel industry. Arcelor Mittal has committed to operating in its units in a responsible manner and has taken care of the health, safety and welfare of its employees. At the same time, it is committed to acting with respect to sustainable development.